Accuracy of heart-rate-recovery parameters assessed from a wrist-worn photoplethysmography monitor (Polar Unite) - Bretonneau, Q.; Peruque-Gayou, E.; Wolfs, E.; Bosquet, L. (International Journal of Sports Physiology and Performance, 2024)
Purpose: The accuracy of heart rate (HR) measured with a wrist-worn photoplethysmography (PPG) monitor is altered during rest-exercise and exercise-rest transitions, which questions the validity of postexercise HR-recovery (HRR) parameters estimated from this device.